Marco Polo, Nicknamed the Million, and His “Book on the Diversity of the World” - A.N. Garkavets (Золотоордынское обозрение)
Objective: To highlight the most urgent problems related to the person of Marco Polo and his works, written in collaboration with Rustichano (commonly known as Rustichello) of Pisa. Research materials: the work of Marco Polo, with attention drawn to its general characteristics and scientific value. Materials are used which describe the history of the Polo family and the biography of Marco Polo the traveler. This work explores the routes of Polo’s travels, his career success in China and his documentary information about the country in the era of the Mongol Yuan Dynasty. We explore his language proficiency, in particular regard to the “Tatar” language in light of the source for the “Tatar” Lord Prayer in edition of Marco Polo in a German translation of Jerome Megizer; the return-route from China to Ilkhanate of the Hulaguides; the introduction of paper money in Mongol Iran at that time; Marco’s return to Venice and his acquaintance with the novelist, Rustichano of Pisa, while in Genoese captivity; versions of their joint writing on the East; Rustichano and scribes’ additions to the memoirs of Marco; the debated date of the will of Marco Polo and the mystery of two gold items listed in the inventory of his property, which are identified as two of Gaykhatu’s golden paizas; Marco Polo’s connections to the discovery of America by Christopher Columbus and Amerigo Vespucci; fake maps of China, Japan, Sakhalin, the Aleutian Islands, Chukotka, Alaska and much of the North American West, attributed to Marco Polo. Results and novelty of the research: We have confirmed the hypothesis about the origin of the generic nickname Million, received by Polos, and its connection to the estate of the Venetian family, Vilione / Milione. We have identified the source of the “Tatar” Lord Prayer in the German edition of Marco Polo. We have raised the question of the participation of Polo in the printing of paper money by Gaykhatu. We have proved the forgery of maps which were formerly attributed to Marco Polo.